Education, Disadvantage and Place : Making the Local Matter - Dyson, Alan (Book collections on Project MUSE., 2014)
Challenging current thinking, this important book is the first to focus on the role of area-based initiatives to tackle the link between education, disadvantage and place. Aimed at all those actively seeking to tackle disadvantage, including policymakers, practitioners, academics and students.